OR Practice—Application of a Probabilistic Decision Model to Airline Seat Inventory Control - Belobaba, Peter P. (Operations Research, 1989)
The application of booking limits on the number of seats available at different prices on the same flight allows airlines to increase revenues. Effective seat inventory control by an airline depends on forecasts of future bookings, the revenue values associated with each fare type, and an ability to make systematic tradeoffs between booking requests so as to maximize total flight revenues. This article describes the implementation of a computerized system for making these tradeoffs and setting booking limits on future flights at Western Airlines in early 1987. The Expected Marginal Seat Revenue (EMSR) decision model developed for this application takes account of the uncertainty associated with estimates of future demand as well as the nested structure of booking limits in airline reservations systems. The Automated Booking Limit System implemented at Western made use of the EMSR model to set and revise booking limits periodically prior to flight departure. Although the system did not take into account several important components of the seat inventory control problem, a revenue impact test on a sample of actual flights showed a significant revenue improvement over the judgmental methods used previously.